Blue Native Polyacrylamide Gel Electrophoresis (BN‐PAGE) for the Analysis of Protein Oligomers in Plants. Issue 2 (6th April 2020) - Na Ayutthaya, Pratchaya Pramoj; Lundberg, Derek; Weigel, Detlef; Li, Lei
Abstract: Protein‐protein interactions, including oligomerization, are involved in regulation of many cellular processes. Unfortunately, many proteins are expressed at a very low level in vivo, making it challenging to observe oligomerization by size‐exclusion chromatography, also known as gel filtration. In this protocol, we present detailed steps to perform blue native polyacrylamide gel electrophoresis (BN‐PAGE), a method to study protein oligomers in plants. The article describes protein sample preparation from transgenic Arabidopsis thaliana and running a BN‐PAGE gel followed by direct western blotting or, alternatively, two‐dimensional sodium dodecyl sulfide–polyacrylamide gel electrophoresis (2D SDS‐PAGE). This protocol will be helpful for new researchers conducting related experiments to analyze stable protein interactions including homo‐ or hetero‐oligomerization in plants. © 2020 The Authors.